O papel da via Sonic Hedgehog (Shh) na padronização e regeneração de nadadeiras do peixe pulmonado africano Protopterus annectens - SANTOS, Erika Monteiro dos (2022)
The lungfishes are valuable models to understand the transition from the aquatic to the terrestrial environment during the evolution of tetrapods organisms. The lungfish Protopterus annectens is a Sarcopterygii fish (sister group of Tetrapoda), which has vestigial distal radials localizated in the pectoral fin hem. The tetrapods and the sarcopterygian fishes share a protein known as Sonic Hedgehog (SHH), which is responsible for the formation of distal radials in fishes and the digits in tetrapods. Studies have shown that Shh is critical during the development of tetrapods, changes in the levels of this protein can lead to malformations, especially in the digits. This protein also has a fundamental role during the regeneration of the limbs, in salamanders the ectopic activation of SHH causes phenotypes such as polydactyly. Therefore, our hypothesis questions whether SHH functions are shared in the establishment of distal radials of lungfishes and it is a probable deep homology with the digits of tetrapods, since it shares specific molecular mechanisms used to build structures with no apparent phylogenetic or morphological relationship. Therefore, the objective of this work is to analyze the role of the SHH pathway in the regeneration and patterning of the african lungfish P. annectens. The present study was carried out through amputations of the fins of P. annectens, which were treated with drugs that directly interfere in the SHH pathway, the agonist molecule (SAG) and the antagonist (Cyclopamine), in different stages of regeneration, making it is possible to analyze the role of the SHH signaling pathway for regeneration to occur, with a primary focus on the formation of distal radials present in the fin. As a conclusion, our results suggest the existence of a deep homology between distal radials in fishes and digits of tetrapods, considering that both structures need SHH for their formation.